Electrical Installations. Book 1, Level 3 apprenticeship (5357), level 2 technical certificate (8202), level 2 diploma (2365) - Tanner, Peter (London : Hodder Education, 2018)
Equip yourself with the tools for success in Electical Installations with this this comprehensive new textbook published in association with City & Guilds and IET which has been fully-updated in line with the 2018, 18th Edition wiring regulations.
Includes Internet access.
Includes index.
Keywords: Electric apparatus and appliances -- Installation -- Great Britain; Technology